Female speech style : Does it change over time? / Kamisah Ariffin, Misyana Susanti Husin and Roselina Musahar - Ariffin, Kamisah; Husin, Misyana Susanti; Musahar, Roselina (Universiti Teknologi MARA Cawangan Pahang, 2004)
Numerous examinations of gender speech styles have been conducted primarily based on real life conversations which were unprepared and spontaneous (Coates 1986; Tannen 1991; Githens 1991), but little has been done in other frameworks. This study looks at gender speech styles in the perspective of its portrayal in literary texts. It focuses on the analysis of stereotyped characteristics of female speech style as portrayed in three children’s novels, written over a period of three centuries – 19th, 20th and 21st Centuries. The analysis is based on Lakoff’s characteristics of female speech style – the use of special vocabulary, imprecise intensifiers, super polite forms, weak forms of expletives, hedges, tag questions and direct quotations, as portrayed in the novels. Since most creative writings are created based on the writers’ observations on the reality of their surroundings, to a certain extent, they do rely on the stereotyped and generalized behaviour to make their written products believable, real and acceptable to the audience. Thus, this study also examines whether the female style of speaking changes over time, based on the writers’ observations and perceptions.